Thermodynamics and complex dielectric permittivity of mixed crystals of the Rb₁-x(NH₄)xH₂PO₄ type - Levitsky, R.R.; Sorokov, S.I.; Stankowski, J.; Trybula, Z.; Vdovych, A.S. (Condensed Matter Physics, 2008)
We propose a pseudospin model for proton glasses of the Rb₁₋x(NH₄)xH₂PO₄(Rb₁₋x(ND₄)xD₂PO₄) type, which takes into account the energy levels of hydrogens (deuterons) around the PO₄ group, long-range interactions between the hydrogen bonds, and an internal random deformational field. Within the framework of a cluster approximation and a mean field approximation over the long-range interactions, we derive a system of equations for the state parameters for the regions which are in the ferroelectric and antiferroelectric states, as well as in the proton glass state. Within the Glauber dynamics approach, we obtain a system of equations for the frequency-dependent linear responses of polarization and the proton glass order parameter. We obtain a qualitative description of the temperature behavior of dielectric permittivities of the K₁₋x(ND₄)xD₂PO₄ and Rb₁₋x(NH₄)xH₂AsO₄ compounds at different frequencies. The origin of low-temperature peak in the imaginary part of dielectric permittivity in proton glasses is discussed. Запропонована псевдоспiнова модель протонних стекол типу Rb₁₋x(NH₄)xH₂PO₄(Rb₁₋x(ND₄)xD₂PO₄), яка враховує енергетичнi рiвнi протонiв (дейтронiв) бiля тетраедра PO₄, далекосяжну взаємодiю мiж водневими зв’язками i внутрiшнє хаотичне деформацiйне поле. В рамках кластерного наближення i наближення середнього поля по далекодiїї виведена система рiвнянь для параметрiв стану для областей, якi знаходяться в феро-, антифероелектричному станах, i в станi протонного скла. В рамках глауберiвської динамiки виведена система рiвнянь для частотнозалежних лiнiйних вiдгукiв полярiзацiї i параметра протонного скла. Отримано якiсний опис температурної поведiнки дiелектричних проникностей сполук K₁₋x(ND₄)xD₂PO₄ and Rb₁₋x(NH₄)xH₂AsO₄ при рiзних частотах. Обговорюються причини низькотемпературного пiку уявної частини дiелектричних проникностей в протонних стеклах.